Mr Ellsworth and the Discovery II (Polar Record, 1936)
Leaving Dunedin at 06.00 on January 2 the voyage to the southward was mainly favoured by good weather. This assisted the preparations for those possible emergencies which had to be provided for. Sledges were overhauled and rebound, sledge harnesses were made and rations weighed and packed. The oil fuel which was stowed in drums was gradually pumped below. On an average about 30 drums per day were emptied. The airmen too were constantly busy with their own preparations.